PERENCANAAN BIAYA PRODUKSI KAPAL IKAN 30 GT FIBERGLASS DENGAN SISTEM PENDINGIN FISH HOLD - Rusdy Hatuwe; Amir Marasabessy; Bambang Sudjasta (Bina Teknika, 2017)
Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia in the development of national fishing fleet in an effort to improve the welfare of fishermen and supporting the domestic shipbuilding industry, will build 3000 fiber glass fishing vessels with gross tonnage various fiscal years 2016 to 2019, 2016, 1719 units have been built with a capacity of 3 GT , 5 GT. 10 GT, 20 GT and 30 GT. In planning the production costs (RAB) needs to be examined carefully because during the RAB production of fishing boats fiber glass made reference to the RAB that already exist, if the RAB is too big ship production becomes uneconomic and likely to occur abuse RAB production conversely if too little can affect the quality production ship. The research objective is to make the RAB production of fishing vessels 30 GT-type purse seine with the cooling system of fish hold where materials and equipment/supplies ship components are marine use with a price refers to the exchange rate of the rupiah, which is expected to guarantee the economic value and the quality of the production vessel, The method used in making the RAB is the survey unit price of materials and equipment/supplies components ship with a screw on the design drawings and technical specifications. Based on the results of the study, the cost of manufacture of molded fiber glass fishing boat 30 GT-type purse seine is Rp.278.225.000, - and the cost of ship production (services and material) of Rp.1.944.470.000, -